Review of A causa de la lucha celebrada en San Bartolomé de Geneto (1834), by Víctor Lorenzo Alonso Delgado (Revista de Artes Marciales Asiáticas, 2024)
This book contains the original transcription of a 1834 text about the memory of the judicial process developed from the incidents that occurred during the celebration of a wrestling event in Tenerife. The content of the memory provides information about the forms of organization of the event, the level and mode of standardization of wrestling, terminology or clothing. The text is preceded by a socio-historical introduction about the development of wrestling, embedded within processes of sportisation linked to the generation of a Canarian identity that is distinctive from that of peninsular Spain.